Structuring of sodium tungstate with sodium dodecyl sulphate in aqueous media and its implications for advanced materials development - de Moura, Diego Soares; Vasconcelos, Eduardo Santos; Pazinato, Julia Cristina Oliveira; Defferrari, Diego; Mertins, Omar; da Silva, Emerson Rodrigo; Delgado, Patrick Mathews [UNESP]; Garcia, Irene Teresinha Santos (Elsevier, 2024)
This article explores the structuring sodium tungstate with sodium dodecyl sulphate (SDS) in water and characterizing the resulting products post-destabilization with hydrochloric acid and calcination. Utilizing nuclear magnetic resonance (NMR), small-angle X-ray scattering (SAXS), fluorescence spectroscopy with a pyrene probe, conductivity, and pH analyses, the study elucidates the system's structure and interactions. SDS serves as a structuring agent for tungstate anions in water, with sulphate anions interacting with tungsten d-orbitals. The presence of SDS significantly influences final structures after calcination. Higher precursor/structuring agent ratios result in higher proportion of tungsten oxide, alongside Na2W2O7 and Na2W4O13. Varying calcination temperatures yield different crystal structures and morphologies, including flower petals and roses at 500 °C and nanorods at 700 °C. These findings shed light on material structuring processes. The obtained materials exhibit to utilize solar radiation for chemical reactions.
Keywords: Advanced materials; Auto organization; Polytungstate; Surface chemistry